Descriptive metadata for the newspaper clipping images of the U.P. Institute of Library and Information Science - Corros, Sarah H.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
In order to make newspaper paper clipping images available and more accessible to the users, human intervention is needed to make intelligent image searching possible. This can be done by supplying the applicable metadata to the images. Two main standards are used as tools to determine the applicable metadata for the newspaper clipping image collection. The study focuses on the descriptive concept of metadata standards using Dublin Core. For description, the preliminary framework standard used in MARC21 because it has been used commonly used by librarians for descriptive cataloging. The content standard used is the AACR2r. The decision that Dublin Core is to be used for the final element set is based on the assumption that U.P. will soon be changing its operating system. Dublin Core can be written in HTML which is a universal mark-up language that can be read by any operating system.
The Library of Congress MARC to Dublin Core Crosswalk was used to create a default bibliographic template during the preliminary survey of the images. A total of 466 newspaper clipping images were catalogued after which, the bibliographic template reduced to a metadata template composing of the following metadata elements: Title, Title. Alternative, Creator, Description, Description. Abstract, Type, Format, Format. Extent, Identifier, Language, Relation.IsPartOf.
Two main factors affected the availability of the entries for the elements. One is the external attribute of the image which makes it illegible brought by the processes done during the detachment of the clipping from its source and the scanning process. The other more significant factor is the bibliographic nature of the clipping itself. Entries weren't made for corresponding elements simply because the image doesn't possess that particular corresponding element.
It is recommended that cataloguing should be done before the clipping is detached from its source. This would allow the cataloguer to obtain as much bibliographic description from the item as possible so that no data about the item will be lost due to illegibility and other external attributes. It would also help the cataloguer if standards for detaching and scanning the clippings would be determined if cataloguing is to be done after physically detaching the clipping from its source.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Metadata -- University of the Philippines Institute of Library and Information Science; Clippings (Books, newspapers, etc.).